2005
DOI: 10.1002/cncr.21612
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome after low‐grade astrocytoma treatment in childhood

Abstract: The hydrogels assembled from a pair of self‐repulsive but mutually attractive decapeptides are visualized by magnetic resonance imaging (MRI). It is found that in the absence of Gd(III)‐chelate, gelation has little effect on MRI signal intensity. In the presence of Gd(III)‐chelate, gelation leads to significant changes in water relaxation and MR signal intensity. The sol to gel transition is best visualized by T2‐weighted imaging using large echo time with the sol producing a bright spot and the gel producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
126
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(145 citation statements)
references
References 43 publications
11
126
0
6
Order By: Relevance
“…In this study, we did not assess whether our patients were enrolled in special education services such as remedial teaching or whether they repeated classes; future studies shall focus on these aspects to be able to draw more firm conclusion about survivors’ long-term academic welfare. Also, the average follow-up time in this study was 13.29 years (range: 3–21 years); taking a broader follow-up period into account and considering longitudinal instead of cross-sectional data may yield more insight into a phenomenon known as “growing into deficit.” 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we did not assess whether our patients were enrolled in special education services such as remedial teaching or whether they repeated classes; future studies shall focus on these aspects to be able to draw more firm conclusion about survivors’ long-term academic welfare. Also, the average follow-up time in this study was 13.29 years (range: 3–21 years); taking a broader follow-up period into account and considering longitudinal instead of cross-sectional data may yield more insight into a phenomenon known as “growing into deficit.” 6 …”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, at the same time these improved survival rates demand a careful consideration of possible long-term sequelae such as cognitive deficits and functional impairments. A phenomenon commonly referred to as “growing into deficit” 6 highlights the importance of careful follow-ups even for survivors of low-grade CPAs: patients who initially show no deficits may still develop cognitive and functional impairments years after treatment. According to the vulnerability theory, a young age at the time of diagnosis is especially thought to have a detrimental effect on late outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TACQOL is an excellent instrument to assess HRQoL in chronically ill or children surviving a brain tumor and compare findings with the reference population. Multiple studies using the TACQOL are published, including studies in children surviving a brain tumor [7,9,28]. Reliability and validity are sufficient for research purposes.…”
Section: Hrqol Was Measured By the Tno-azl (Netherlands Organisation mentioning
confidence: 99%
“…Monitoring of health-related quality of life (HRQoL) is done, for example, in childhood survivors who are treated for a pilocytic astrocytoma [9][10][11], low-grade glioma [12], high-grade glioma [13], craniopharyngioma [14,15], medulloblastoma [16,17], and in heterogeneous groups [18][19][20][21][22][23][24]. In most of these studies, survivors reported a variety of degree of reduction in HRQoL compared with healthy age mates [9,10,[13][14][15][16][18][19][20][21][22][23][24]. This could be explained by the heterogeneity of brain tumors and their treatments.…”
Section: Introductionmentioning
confidence: 99%